Conversion of waste plastics into fuels: Recycling polyethylene in FCC - de la Puente, Gabriela (2002)
Low density polyethylene was dissolved into toluene and converted at 500 °C over three different commercial FCC catalysts in a laboratory Riser Simulator reactor. Short reaction-times up to 12 s were used. All the catalysts had qualitatively similar behaviors. The specific contribution of the polymer to the product slate of FCC was centered in hydrocarbons in the range of gasoline, with high aromatic content and highly olefinic C3–C4 gases. Saturated C4–C5 products were mainly isoparaffins. The additional coke formed by the polymer would make coke yields to increase moderately in relation to the standard operation. These facts confirmed that this recycling option, which is based on a proven technology, represents an interesting alternative to solve a major environmental problem.